Los Raids de Aventura como motor dinamizador de entornos naturales en Extremadura - Morenas Martín, Jesús; del Campo, Vicente Luis (Eracle. Journal of Sport and Social Sciences, 2019)
The region of Extremadura, as other zones in Spain, has carried out different plans for the development of natural areas in the last decades, such as the protection of natural spaces. These programs have had some impact on society, but they have not prevented the gradual depopulation of the rural territory. This problem is bigger if we add the reduction of the activities related to the primary sector such as the agriculture and livestock. In this context, new opportunities have emerged for the development of sectors or activities of social and cultural nature, such as the physical activities in the natural environment or active tourism. The multi-adventure raids are sport competitions which include a multitude of participants performing orientation races through a large area of natural environment, mainly on foot or by mountain bike. This activity also includes other disciplines such as climbing, rappel, archery, zip lines, offering different physical activities for the general public. Extremadura has developed its own league of raids (LEXRA), hosting several national tests of these sport events and attracting many participants. This sustainable and friendly activity with the natural environment is a great tool for the boosting of natural spaces. For this reason, many villages are already committed in the development of these sports events to boost natural spaces, having a social benefit and an impact for their economy.